Psychological well-being: The impact of student perceptions on guidance and counseling teachers - Kurniawan, Luky; Suwidagdho, Dhanang; Ningsih, Ruly (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
The increasingly complex problem becomes a challenge for guidance and counselling teachers or counsellors as professional helpers. The ideal guidance and counselling teacher or counsellor figure is expected to answer the challenges of the current millennial era. The objectives to be achieved in this study are to obtain an overview of students' perceptions of the ideal guidance and counselling teacher and to find out the relationship between student perceptions and the level of welfare of Senior High School students. The research subjects of Senior High School students in Yogyakarta. The object of this research is, Perceptions of students, Figure of ideal guidance and counselling teachers, The level of well-being of students at Senior High School students in Yogyakarta. The method used for data collection using a questionnaire. The results showed a significant relationship between student perceptions of guidance and counselling teacher figures with the level of psychological well-being in schools. The counsellor's ability to understand himself and see a problem from the point of view of others will have an impact on students' perceptions of the counsellor. These results imply the importance of guidance and counselling teachers to continue to develop professionalism in schools so that students can be served well, and have an impact on the psychological well-being of students.